2016
DOI: 10.1515/phys-2016-0055
|View full text |Cite
|
Sign up to set email alerts
|

Droplet spreading and permeating on the hybrid-wettability porous substrates: a lattice Boltzmann method study

Abstract: Abstract:The spreading and permeation of droplets on porous substrates is a fundamental process in a variety of applications, such as coating, dyeing, and printing. The spreading and permeating usually occur synchronously but play different roles in the practical applications. The mechanisms of the competition between spreading and permeation is significant but still unclear. A lattice Boltzmann method is used to study the spreading and permeation of droplets on hybrid-wettability porous substrates, with diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…In contrast with our results, simulations by Reis et al [43] found that a lower contact angle reduced the spreading ratio. Nevertheless, other Lattice-Boltzmann studies done by [41,44], and [42] performed on simplified porous media (regular grid of cylindrical or square pores) have also shown that a lower contact angle increases the spreading rate. The disagreement between the former numerical model [43] and the Lattice-Boltzmann studies can be explained by a different model used for describing the contact angle dynamics and the surface wettability.…”
Section: Resultsmentioning
confidence: 94%
“…In contrast with our results, simulations by Reis et al [43] found that a lower contact angle reduced the spreading ratio. Nevertheless, other Lattice-Boltzmann studies done by [41,44], and [42] performed on simplified porous media (regular grid of cylindrical or square pores) have also shown that a lower contact angle increases the spreading rate. The disagreement between the former numerical model [43] and the Lattice-Boltzmann studies can be explained by a different model used for describing the contact angle dynamics and the surface wettability.…”
Section: Resultsmentioning
confidence: 94%
“…Ambient conditions greatly influence the absorption process and can modify the mass transfer by orders of magnitude. Furthermore, interaction with the wall has a major impact on droplet properties and the gas-fluid interaction [18]. A significant amount of research has been done on the topic of interface mass transfer during the better part of the last century [19], but a simple and comprehensive unified model is still not available.…”
Section: Mass Transfer Dynamicsmentioning
confidence: 99%
“…These models provide the design framework for paper-like materials and paper-based devices. Liquid flow in paper-like materials can be modelled by different approaches: Lucas-Washburn models [15,[17][18][19][20], Darcy's model [21][22][23][24][25] and computational fluid dynamics (CFD) [26][27][28].…”
Section: Introductionmentioning
confidence: 99%